2015
DOI: 10.1007/s12630-015-0502-0
|View full text |Cite
|
Sign up to set email alerts
|

Opioid information pamphlet increases postoperative opioid disposal rates: a before versus after quality improvement study

Abstract: Purpose Half of postoperative patients are prescribed an opioid, but a majority do not store or dispose of them properly thus risking diversion. We examined the efficacy of an opioid educational pamphlet addressing opioid weaning, storage, and disposal. We hypothesized that the pamphlet would increase the rate of proper opioid disposal, storage, and weaning. Methods This prospective before and after study was conducted at UBC Hospital in primary total hip or knee arthroplasty patients. Adults with American Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 15 publications
1
56
0
Order By: Relevance
“…Steroids have also been shown to be a promising component of multimodal analgesia, most likely through anti‐inflammatory effects . Additionally, preoperative education on pain management may decrease postoperative opioid consumption by setting patient expectations for treatment outcomes . Lastly, effective inpatient multimodal pain regimens may decrease the need for opioids in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Steroids have also been shown to be a promising component of multimodal analgesia, most likely through anti‐inflammatory effects . Additionally, preoperative education on pain management may decrease postoperative opioid consumption by setting patient expectations for treatment outcomes . Lastly, effective inpatient multimodal pain regimens may decrease the need for opioids in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…The educational program was designed to address the inadequate knowledge regarding opioids demonstrated by our patients in a previous survey. Several studies have shown various levels of success using different modalities to improve patient education and other outcomes . Our group decided to use a pamphlet as our EM (along with personalized education by our PC clinic medical staff) because of its straightforwardness, ease of implementation, and reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the important role that consistent and simple education initiatives play in improving safe opioid practices in targeted patients . In a similar study surveying adult patients who had undergone hip and knee replacement surgery, providing education pamphlets showed improvement in the number of patients who practiced proper disposal but no improvement in safe storage practice . One randomized controlled trial looking into the impact of an educational intervention that included education materials on hydrocodone, followed by phone calls conducted 4 to 7 days after the visit to assess patient knowledge of the drug, reported that this intervention improved knowledge about the drug and reduced the incidence of driving while on the medication .…”
Section: Measures To Address Opioid Use Storage and Disposal Issuesmentioning
confidence: 99%